A better man : a (mostly serious) letter to my son - Black, Michael Ian, 1971- (Algonquin Books of Chapel Hill, 2020)
"Michael Ian Black takes a poignant look at manhood, written in the form of a heartfelt letter to his teenage son before he leaves for college. Black offers a radical plea for rethinking masculinity and teaching young men to give and receive love"--